Observed kinetics for the production of diethyl carbonate from CO2 and ethanol catalyzed by CuNi nanoparticles supported on activated carbon (2024)
Monometallic and bimetallic Cu:Ni catalysts with diferent Cu:Ni molar ratios (3:1, 2:1, 1:1, 1:2, 1:3) were synthesized by wetness impregnation on activated carbon and characterized by TPR (temperature programmed reduction), XRD (X-ray difraction) and XPS (X-ray photoelectron spectroscopy). The synthesized catalysts were evaluated in the gas phase production of diethyl carbonate from ethanol and carbon dioxide. The largest catalytic activity was obtained over the bimetallic catalyst with a Cu:Ni molar ratio of 3:1. Its improved activity was attributed to the formation of a Cu–Ni alloy on the surface of the catalyst, evidenced by XPS and in agreement with a previous assignment based on Vegard law and TPR analysis. During the reaction rate experiments, it observed the presence of a maximum of the reaction rate as a function of temperature, a tendency also reported for other carbon dioxide–alcohol reactions. It showed that the reaction rate-temperature data can be adjusted with a reversible rate equation. The initial rate as a function of reactant partial pressure data was satisfactorily adjusted using the forward power law rate equation and it was found that the reaction rate is frst order in CO2 and second order in ethanol.